PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENTS (TGT) DALAM MENINGKATKAN HASIL BELAJAR SERVIS ATAS BOLA VOLI KELAS XI-1O SMAN 21 SURABAYA - Fitra Hafidhi, Nafkhan; Zidane Al Mughni, M; Ariansah, R; Rifaldo B S, M; Zakki R M, M; TAMAMMUDIN, MUHAMMAD; Himawan Susanto, Indra; Widagdo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the improvement in students' volleyball Classroom Action Research (CAR) outcomes through the Team Game Tournament (TGT) cooperative learning model. This study was conducted in two cycles, each divided into four stages: planning, action, observation, and reflection. The subjects of this classroom action research were 31 students in grade XI-10 of SMAN 21 Surabaya, consisting of 15 boys and 16 girls. Data collection was conducted using test data and observations. Data validity was validated using data triangulation techniques. The results of this study indicate that the TGT cooperative learning model improved volleyball overhead serve learning outcomes from cycle I to cycle II. In cycle I, there was a 35% increase, or 11 of the 31 students were declared to have completed the volleyball overhead serve. A 90% increase in volleyball overhead serve performance also occurred in cycle II, with 28 students meeting the completion standard of 84 and 3 students failing